2012
DOI: 10.1111/j.2042-7158.2012.01573.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two polymorphs of lornoxicam

Abstract: Form II had the significantly higher solubility and dissolution and would be the suitable polymorph for the preparation of oral and injectable dosage forms of lornoxicam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…(6-Chloro-4-hydroxy-2-methyl-N-2-pyridinyl-2H-thieno[2,3-e]-1,2thiazine-3-carboxamide 1,1-dioxide, C13H10ClN3O4S2, Fig.1) is a non-steroidal antiinflammatory drug (NSAID) that belongs to the "oxicam" class, which presents analgesic, anti-inflammatory and antipyretic properties [1,2,3]. It is used in musculoskeletal and joint disorders such as osteoarthritis and rheumatoid arthritis.…”
Section: Lornoxicammentioning
confidence: 99%
“…(6-Chloro-4-hydroxy-2-methyl-N-2-pyridinyl-2H-thieno[2,3-e]-1,2thiazine-3-carboxamide 1,1-dioxide, C13H10ClN3O4S2, Fig.1) is a non-steroidal antiinflammatory drug (NSAID) that belongs to the "oxicam" class, which presents analgesic, anti-inflammatory and antipyretic properties [1,2,3]. It is used in musculoskeletal and joint disorders such as osteoarthritis and rheumatoid arthritis.…”
Section: Lornoxicammentioning
confidence: 99%
“…3 . Lornoxicam exits in two polymorphic forms ( Zhang et al, 2013 ). XRD patterns resembled that of polymorph form II with sharp peaks appearing at 22.03°, 23.82°, 26.06°, 30.35° and 33.49° at the 2-theta scale, corresponding to crystalline nature of lornoxicam.…”
Section: Resultsmentioning
confidence: 99%
“…The solubility of lornoxicam showed strong pH dependence, as the solubility increased along with the pH step up. [18] The stability of lornoxicam for injection in 0.9% sodium chloride injection prepared according to clinical regime showed that no significant change in 72 hours. [19] However, drug incompatibility was occurred when lornoxicam combined with butorphanol tartrate or fentanyl citrate injection in 0.9% sodium chloride injection for PCA used.…”
Section: Discussionmentioning
confidence: 99%